Characterization of Poly(Acrylic) Acid-Modified Heterogenous Anion Exchange Membranes with Improved Monovalent Permselectivity for RED - Ivan Merino-Garcia; Francis Kotoka; Carla A.M. Portugal; João G. Crespo; Svetlozar Velizarov (Membranes, 2020)
The performance of anion-exchange membranes (AEMs) in Reverse Electrodialysis is hampered by both presence of multivalent ions and fouling phenomena, thus leading to reduced net power density. Therefore, we propose a monolayer surface modification procedure to functionalize Ralex-AEMs with poly(acrylic) acid (PAA) in order to (i) render a monovalent permselectivity, and (ii) minimize organic fouling. Membrane surface modification was carried out by putting heterogeneous AEMs in contact with a PAA-based aqueous solution for 24 h. The resulting modified membranes were firstly characterized by contact angle, water uptake, ion exchange capacity, fixed charge density, and swelling degree measurements, whereas their electrochemical responses were evaluated through cyclic voltammetry. Besides, their membrane electro-resistance was also studied via electrochemical impedance spectroscopy analyses. Finally, membrane permselectivity and fouling behavior in the presence of humic acid were evaluated through mass transport experiments using model NaCl containing solutions. The use of modified PAA-AEMs resulted in a significantly enhanced monovalent permselectivity (sulfate rejection improved by >35%) and membrane hydrophilicity (contact angle decreased by >15%) in comparison with the behavior of unmodified Ralex-AEMs, without compromising the membrane electro-resistance after modification, thus demonstrating the technical feasibility of the proposed membrane modification procedure. This study may therefore provide a feasible way for achieving an improved Reverse Electrodialysis process efficiency.